An Introduction to Structural Mechanics for Architects - Cueto, Elías (Structural Integrity, 2018)
This textbook offers an introductory course to structural mechanics for architects, including problems and solutions. It follows a completely different approach to structural mechanics than the usual books for engineering schools, making it much more attractive for architecture students and practitioners. It also offers a different point of view for engineering students, as it provides them with a more intuitive understanding of structural mechanics and the models therein. Instead of studying the classical theory of linear elasticity and then particularizing it to simple structures, this book analyzes structures in a historic and also typological order. The book starts with cable structures and stone arches, followed by trusses and, finally, frame structures made of beams. For every typology, the latest, state-of-the-art theory in the field is introduced in a very didactic way.